Case Report: Possible Vertical Transmission of Bartonella bacilliformis in Peru - Tuya, XL (2015)
A 22-day-old male was admitted with a 2-day history of irritability, dyspnea, jaundice, fever, and gastroin testinal bleeding. A thin blood smear was performed, which showed the presence of intraerythrocyte bacteria identified as Bartonella bacilliformis, and subsequently, the child was diagnosed with Carrion’s disease. The diagnosis was confirmed by specific polymerase chain reaction. The child was born in a non-endemic B. bacilliformis area and had not traveled to such an area before hospitalization. However, the mother was from an endemic B. bacilliformis area, and posterior physical examination showed the presence of a wart compatible with B. bacilliformis in semi-immune subjects.These data support vertical transmission of B. bacilliformis.